Emerging Therapeutic Approaches for the Disruption and Control of Pseudomonas Biofilms: Mechanisms and Applications (Development Engineering Conferences Center Articles Database, 2025)
Pseudomonas biofilms present significant challenges in both medical and industrial settings, contributing to persistent infections and equipment degradation. Emerging therapeutic approaches for disrupting and controlling Pseudomonas biofilms are critical for addressing these issues. This review examines the latest advancements in biofilm disruption strategies, focusing on novel pharmacological agents, nanomaterials, and gene-editing techniques. The mechanisms underlying biofilm formation and resistance to conventional treatments are explored, alongside cutting-edge methods aimed at overcoming these challenges. Additionally, the clinical and industrial applications of these therapies are discussed, highlighting their potential to improve treatment outcomes and reduce biofilm-related damage. The findings suggest that a combination of targeted therapies, along with a better understanding of biofilm dynamics, can lead to more effective management of Pseudomonas-associated infections and biofilm formation in various environments.